'I owe it to my group members…who critically commented on my conducting' – Cooperative learning in choral conducting education. (February 2016) - Varvarigou, Maria
This article explores cooperative learning in choral conducting education. The five characteristics of cooperative learning identified by Adams and Hamm ((1996). Cooperative learning: Critical thinking and collaboration across the curriculum (2nd ed.). Springfield, IL: Charles Thomas Publishers): positive interdependence; face-to-face interaction; individual accountability and personal responsibility for reaching groups goals; frequent practice with small-group interpersonal skills; and regular group processing and reflection have been used to structure the discussion on the learners' perception of their development and their module's effectiveness. The context in focus was an elective module on choral conducting education at master's level. Cooperative learning in choral conducting education was shown to support the learners' motivation for active participation in the teaching and learning process; to increase respect for diversity; to support the learners' development of interpersonal, communication, leadership and teaching skills at both an individual and at a collective level; and to improve teacher effectiveness.